The roles of BTG1 mRNA expression in cancers: A bioinformatics analysis - Zheng, Hua-chuan; Xue, Hang; Zhang, Cong-yu; Shi, Kai-hang; Zhang, Rui (Frontiers in Genetics, 2022)
BTG1 (B-cell translocation gene 1) may inhibit proliferation and cell cycle progression, induce differentiation, apoptosis, and anti-inflammatory activity. The goal of this study was to clarify the clinicopathological and prognostic significances of BTG1 mRNA expression and related signal pathways in cancers. Using the Oncomine, TCGA (the cancer genome atlas), xiantao, UALCAN (The University of ALabama at Birmingham Cancer data analysis Portal), and Kaplan-Meier plotter databases, we undertook a bioinformatics study of BTG1 mRNA expression in cancers. BTG1 expression was lower in gastric, lung, breast and ovarian cancer than normal tissue due to its promoter methylation, which was the opposite to BTG1 expression. BTG1 expression was positively correlated with dedifferentiation and histological grading of gastric cancer (p < 0.05), with squamous subtype and young age of lung cancer (p < 0.05), with infrequent lymph node metastasis, low TNM staging, young age, white race, infiltrative lobular subtype, Her2 negativity, favorable molecular subtyping, and no postmenopause status of breast cancer (p < 0.05), and with elder age, venous invasion, lymphatic invasion, and clinicopathological staging of ovarian cancer (p < 0.05). BTG1 expression was negatively correlated with favorable prognosis of gastric, lung or ovarian cancer patients, but the converse was true for breast cancer (p < 0.05). KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis showed that the top signal pathways included cytokine-cytokine receptor interaction, cell adhesion molecules, chemokine, immune cell receptor and NF (nuclear factor)-κB signal pathways in gastric and breast cancer. The top hub genes mainly contained CD (cluster of differentiation) antigens in gastric cancer, FGF (fibroblast growth factor)-FGFR (FGF receptor) in lung cancer, NADH (nicotinamide adenine dinucleotide): ubiquinone oxidoreductase in breast cancer, and ribosomal proteins in ovarian cancer. BTG1 expression might be employed as a potential marker to indicate carcinogenesis and subsequent progression, even prognosis.